Jak badać murale z perspektywy socjologicznej? Przykład Łodzi - Piotr Mikołaj Statucki, Piotr Mikołaj Statucki (Człowiek i Społeczeństwo, 2019)
The article explores the study of murals from the point of view of sociology and shows its application, taking the city of Lodz as an example. The proposed perspective is divided into three, partly overlapping sections: artistic, management and organizational areas. It is an attempt to present the methods used in the researches on murals and test them adopting the said division. The purpose of the text includes presenting how murals are perceived by different groups – viewers, art institutions, local media and city government. The research draws attention to the question of maintaining a balance between quantity and quality of art in public space.